The Formulation of The Norm On Handling The Violation of Local Election - Bura Datu, Atiqah Mumtazah Ameliah (Jurnal Mulawarman Law Review, 2018)
The study to analyze the formulation of the norm on handling the violations of local election which can affirm sanctions for violators of Article 73 of Law Number 10 of 2016 concerning the Second Amendment to the Act Number 1 of 2015 regarding the Government Regulation in Lieu of Act Number 1 of 2014 about the Election of Governors, Regents and Mayors into Law. The Type of the Research Method used in this study is normative legal research. The results of this study are the sanction formulation policies specifically regarding the formulation of administrative sanctions for violators of Article 73 of Act Number 10 of 2016 regarding The Election of Governors, Regents and Mayors, which have a number of fundamental weaknesses, thus affecting the effectiveness of handling violation, because the weaknesses in the formulation stage (in abstracto) are strategic weaknesses for the next stage, namely the application and execution stage (in concret). The conclusion of this study is that there is a legal certainty about the violation handling for the local election that is structured, systematic and massive. It is recommended that these elements are not to be used as a series of reasons that will be difficult in proving all three together since it will cause legal uncertainty and a short amount of time to handle an election crime, the bureaucracy to handle election crimes should be designed more simply.